Relationship between Femoral Offset and Dislocation in Preformed Antibiotic-Loaded Cement Spacers (Spacer-G®). Issue 5 (September 2017) - Molinas, Ignacio; Garcia-Oltra, Ester; Fernández-Valencia, Jenaro A.; Tomas, Xavier; Gallart, Xavier; Riba, Josep; Combalia, Andreu; Bori, Guillem
Introduction: A reduction in femoral offset may decrease muscle tension and lead to spacer dislocations even though proximal femur, musculature and acetabulum remain intact. In this study, we aimed to determine whether postoperative lateral femoral offset (LFO) and modified vertical femoral offset (MVFO) values affect the risk of dislocation of a hip spacer. Materials and methods: We measured LFO and MVFO in properly centred, postoperative, anteroposterior radiographs of the pelvis in 66 patients (71 spacers). We then compared the operated and non-operated sides and recorded any dislocations. Results: Although LFO decreased (p<0.001), the reduction was not associated with dislocation (p = 0.471). MVFO remained unchanged after spacer implantation (p = 0.277) and was not associated with dislocation (p = 0.418). Conclusions: In conclusion, the preformed spacer decreased LFO but not MVFO compared with the contralateral hip. The variations did not significantly affect the dislocation rate.